Should teachers be colorblind? How multicultural and egalitarian beliefs differentially relate to aspects of teachers' professional competence for teaching in diverse classrooms. (May 2015) - Hachfeld, Axinja; Hahn, Adam; Schroeder, Sascha; Anders, Yvonne; Kunter, Mareike
Abstract: This study uses the framework of professional competence to investigate the relationship between two cultural beliefs, multiculturalism and colorblindness, and different aspects of professional competence for teaching immigrant students. Results from path model analyses with 433 beginning teachers showed that participants with multicultural beliefs reported higher motivational orientations (self-efficacy and enthusiasm for teaching, and more integrative career motives), more positive values (lower agreement with negative stereotypes), and more reported willingness to adapt their teaching. Colorblind beliefs showed no relationships to the former constructs and were negatively related to reported willingness to adapt teaching to culturally diverse students. Highlights: We investigated how cultural beliefs relate to aspects of professional competence. The cultural beliefs studied were multiculturalism (MC) and colorblindness (CB). Paths analyses with 433 beginning teachers showed differential results. Only MC was positively related to motivational orientations and positive values. CB was negatively related to willingness to adapt teaching to diversity.